Potential Impact of Rapid Blood Culture Testing for Gram-Positive Bacteremia in Japan with the Verigene Gram-Positive Blood Culture Test. (20th February 2017) - Kikuchi, Ken; Matsuda, Mari; Iguchi, Shigekazu; Mizutani, Tomonori; Hiramatsu, Keiichi; Tega-Ishii, Michiru; Sansaka, Kaori; Negishi, Kenta; Shimada, Kimie; Umemura, Jun; Notake, Shigeyuki; Yanagisawa, Hideji; et al.
Abstract : Background. Early detection of Gram-positive bacteremia and timely appropriate antimicrobial therapy are required for decreasing patient mortality. The purpose of our study was to evaluate the performance of the Verigene Gram-positive blood culture assay (BC-GP) in two special healthcare settings and determine the potential impact of rapid blood culture testing for Gram-positive bacteremia within the Japanese healthcare delivery system. Furthermore, the study included simulated blood cultures, which included a library of well-characterized methicillin-resistant Staphylococcus aureus (MRSA) and vancomycin-resistant enterococci (VRE) isolates reflecting different geographical regions in Japan. Methods. A total 347 BC-GP assays were performed on clinical and simulated blood cultures. BC-GP results were compared to results obtained by reference methods for genus/species identification and detection of resistance genes using molecular and MALDI-TOF MS methodologies. Results. For identification and detection of resistance genes at two clinical sites and simulated blood cultures, overall concordance of BC-GP with reference methods was 327/347 (94%). The time for identification and antimicrobial resistance detection by BC-GP was significantly shorter compared to routine testing especially at the cardiology hospital, which does not offer clinical microbiology services on weekends and holidays. Conclusion. BC-GP generated accurate identification and detection of resistance markers compared with routine laboratory methods for Gram-positive organisms in specialized clinical settings providing more rapid results than current routine testing.